UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SEJARAH MELALUI KOMBINASI MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DAN COURSE REVIEW HORAY - Yuliana, Chevia; Musadad, Akhmad Arief; Bachri, Saiful (Candi, 2017)
Thesis,Surakarta: Faculty of Teacher Training and Education, Universitas Sebelas Maret, March 2017.   This research aims to enhance the activeness and student learning outcomes in learning history through the combination of cooperative model, type of Teams Games Tournament and Course Review Horay in the class of X IPS 1 SMA 2 Sukoharjo Academic Year 2016/2017.This research is a classroom action research (CAR). The experiment was conducted in two cycles, with each cycle consisting of the planning stage, action, observation and evaluation / reflection phase. The subjects were students of the class of X IPS 1 SMA Negeri 2 Sukoharjo as much as 35 people. The data source comes from teachers, students, and the learning process. Data collection techniques implemented through orbservations, tests, documentary studies and interviews. Data validity tested through resource triangulation method. Data analyzed using qualitative and quantitative data.The results showed that the activeness and student learning outcomes in the application of combination between cooperative model, type of Teams Games Tournament and Course Review Horay on the teaching of history run as achievement targeted which is 80% of student activeness and 75%.of student learning outcomes. Pre-action student activeness raised from 48,21% to 75,17% in the first cycle and increased to 81,96% in the second cycle. The completeness of student learning outcomes at the pre-action increased from 42,86% to 62,86% in the first cycle and successfully developed to 82,86% in the second cycle.Based on the results and discussion of this research, we can conclude that the combination of the cooperative model, type of Teams Games Tournament and Course Review Horay is able to enhance the activeness and student learning outcomes in the class of X IPS 1 SMA Negeri 2 Sukoharjo Academic Year 2016/2017.